2022
DOI: 10.1002/adma.202106551
|View full text |Cite
|
Sign up to set email alerts
|

Escalating Ferromagnetic Order via Se‐Vacancies Near Vanadium in WSe2 Monolayers

Abstract: as core materials for future spintronics given their potential for high Curie temperature (T C ) and efficient field-tunable magnetic properties. [1][2][3] Despite half-century-long research efforts, the following three primary issues remain unsolved: i) the uncertain origin of ferromagnetism, called phantom ferromagnetism, owing to a lack of structural analysis of nanodefects; [4,5] ii) solubility limit to only a few percent without forming aggregation; [6] and iii) activation of short-range antiferromagnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 39 publications
(64 reference statements)
1
29
0
Order By: Relevance
“…Interestingly, the phase deviation between p-doped SnSe and nonmagnetic SiO 2 /Si substrate is obviously observed, indicating its ferromagnetic order (Supplementary Fig. S21 ), the similar phenomena are also demonstrated in monolayer V-doped WSe 2 35 and monolayer VSe 2 36 . Notably, the single magnetic domain is obtained for p-doped SnSe, which is similar to 2D ferromagnetism Fe 3 GaTe 2 37 .…”
Section: Resultsmentioning
confidence: 53%
“…Interestingly, the phase deviation between p-doped SnSe and nonmagnetic SiO 2 /Si substrate is obviously observed, indicating its ferromagnetic order (Supplementary Fig. S21 ), the similar phenomena are also demonstrated in monolayer V-doped WSe 2 35 and monolayer VSe 2 36 . Notably, the single magnetic domain is obtained for p-doped SnSe, which is similar to 2D ferromagnetism Fe 3 GaTe 2 37 .…”
Section: Resultsmentioning
confidence: 53%
“…The total DOS increase at the Fermi level, larger magnetization, and importantly much enhanced spin density at the interface with overlapping majority and minority regions in the FS of Fe/WSe 2 /Pt HST influence the electronic and spin transport across the interface. The combined effect of all of these factors results in larger spin Seebeck coefficients in HSTs with TMDC layers, which can be useful in interpreting recent experiments reporting enhanced magnetization and spin-resolved transport properties. , ,,, …”
mentioning
confidence: 96%
“…Specifically, a large enhancement of the voltage difference due to the longitudinal spin Seebeck effect in Pt/Ni 81 Fe 19 and Pt/YIG after inserting WS 2 (WSe 2 ) layers has been reported. It was also found that such an increase is dependent on the number of layers in the heterostructure, degree of coverage by the TMDC layers, and quality of the interface. Others have examined spin-dependent transport in Fe 3 O 4 /MoS 2 /Fe 3 O 4 and Co/Al 2 O 3 /MoS 2 junctions. , Spin valves based on spin filtering in WS 2 /Co and NiFe/MoS 2 /NiFe have also been reported. , A gate-tunable magnetic order in WSe 2 by changing the occupation of the Se vacancy states is successfully demonstrated, and computational work investigates the origin of ferromagnetism in complex configurations of Se vacancies in V-doped WSe 2 monolayers . The generated Se vacancies play a key role in the structural change of PdSe 2 because of the laser-induced phase transformation of layered PdSe 2 to metallic phase PdSe 2– x .…”
mentioning
confidence: 99%
See 2 more Smart Citations